2022
DOI: 10.1177/21677026221131309
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Relationship Between Worry and Rumination

Abstract: Clinical scientists disagree about whether worry and rumination are distinct or represent a unitary construct. To inform this debate, we performed a series of meta-analyses evaluating the relationship between worry and different forms of rumination. A total of 719 effect sizes ( N = 69,305) were analyzed. Worry showed a large association with global rumination and with the brooding and emotion-focused subtypes of rumination ( rs = .51–.53). However, even when corrected for measurement error, the correlations d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 109 publications
1
3
0
Order By: Relevance
“…In addition to replication, we aimed to extend the approach to worry in the context of anxiety. We observed a strong correlation between worry and rumination (r=.68, p<0.05) which is consistent with prior findings (e.g., de Jong- Meyer et al, 2009;Segerstrom et al, 2000;Stade & Ruscio, 2023). It has been suggested that this overlap captures the common negative repetitive thinking process (Taylor & Snyder, 2021).…”
Section: Worry Networksupporting
confidence: 91%
“…In addition to replication, we aimed to extend the approach to worry in the context of anxiety. We observed a strong correlation between worry and rumination (r=.68, p<0.05) which is consistent with prior findings (e.g., de Jong- Meyer et al, 2009;Segerstrom et al, 2000;Stade & Ruscio, 2023). It has been suggested that this overlap captures the common negative repetitive thinking process (Taylor & Snyder, 2021).…”
Section: Worry Networksupporting
confidence: 91%
“…Our study had several strengths. We used a mixed clinical sample, which is known to increase statistical power by capturing the widest possible range of severity scores (Stade & Ruscio, 2023). We also performed rigorous tests for specificity using high-quality measures of depression and anxiety.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Worry can compromise emotional well-being because it is usually accompanied by rumination, which involves repetitive cognitive processes that focus on negative possibilities and potential threats. 15 This cognitive rumination can lead to increased levels of anxiety and stress, which in turn can negatively impact current psychological well-being. 16,17 In China, in 2015, the number of individuals aged 65 or older was approximately 144 million, which accounted for 10.5% of the total population.…”
Section: Introductionmentioning
confidence: 99%
“…Worrying about future medical care may be based on older adults' self‐evaluation of their own ability to access the quality medical care they need, which is common among those with inadequate health literacy. Worry can compromise emotional well‐being because it is usually accompanied by rumination, which involves repetitive cognitive processes that focus on negative possibilities and potential threats 15 . This cognitive rumination can lead to increased levels of anxiety and stress, which in turn can negatively impact current psychological well‐being 16,17 …”
Section: Introductionmentioning
confidence: 99%